Composition of soil bacterial and fungal communities in relation to vegetation composition and soil characteristics along an altitudinal gradient - Bayranvand, Mohammad; Akbarinia, Moslem; Salehi Jouzani, Gholamreza; Gharechahi, Javad; Kooch, Yahya; Baldrian, Petr (FEMS microbiology ecology, 2021)
The objective of the present study was to evaluate how altitudinal gradients shape the composition of soil bacterial and fungal communities, humus forms and soil properties across six altitude levels in Hyrcanian forests. Soil microbiomes were characterized by sequencing amplicons of selected molecular markers. Soil chemistry and plant mycorrhizal type were the two dominant factors explaining variations in bacterial and fungal diversity, respectively. The lowest altitude level had more favorable conditions for the formation of mull humus and exhibited higher N and Ca contents. These conditions were also associated with a higher proportion of Betaproteobacteria, Acidimicrobia, Acidobacteria and Nitrospirae. Low soil and forest floor quality as well as lower bacterial and fungal diversity characterized higher altitude levels, along with a high proportion of shared bacterial (Thermoleophilia, Actinobacteria and Bacilli) and fungal (Eurotiomycetes and Mortierellomycota) taxa. Beech-dominated sites showed moderate soil quality and high bacterial (Alphaproteobacteria, Acidobacteria, Planctomycetes and Bacteroidetes) and fungal (Basidiomycota) diversity. Particularly, the Basidiomycota were well represented in pure beech forests at an altitude of 1500 m. In fertile and nitrogen rich soils with neutral pH, soil quality decreased along the altitudinal gradient, indicating that microbial diversity and forest floor decomposition were likely constrained by climatic conditions.
Keywords: houby; hyrcanian forests; Soil Microbiology; bacteria and fungi; mykobiom; Mycorrhizae; mykorhiza; metabarcoding; Mycobiome; Soil; půdní mikrobiologie; microbial communities; Bacteria; plant-microbe-soil interactions; Fungi; lesy; půda; Forests